2016
DOI: 10.1051/epjconf/201612204002
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of nuclear transmutation by negative muon capture reaction using the PHITS code

Abstract: Abstract. Feasibility of nuclear transmutation of fission products in high-level radioactive waste by negative muon capture reaction is investigated using the Particle and Heave Ion Transport code System (PHITS). It is found that about 80 % of stopped negative muons contribute to transmute target nuclide into stable or short-lived nuclide in the case of 135 Cs, which is one of the most important nuclide in the transmutation. The simulation result also indicates that the position of transmutation is controllab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Abe et al . also studied RI productions by the muon capture reaction and assessed its feasibility for nuclear transmutation [49], using PHITS code [50]. They also concluded that a high intensity of negative muon source is required for transmutation by negative muon capture reaction.…”
Section: Feasibility Of 99 Mo Production By Muon Capturementioning
confidence: 99%
“…Abe et al . also studied RI productions by the muon capture reaction and assessed its feasibility for nuclear transmutation [49], using PHITS code [50]. They also concluded that a high intensity of negative muon source is required for transmutation by negative muon capture reaction.…”
Section: Feasibility Of 99 Mo Production By Muon Capturementioning
confidence: 99%